Labor Unions and Product Quality Failures - Kini, Omesh; Shen, Mo; Shenoy, Jaideep; Subramaniam, Venkat (Management Science, 2022)
In this paper, we study the impact of labor unions on product quality failures. We use a product recall as our measure of quality failure because it is an objective metric that is applicable to a broad cross-section of industries. Our analysis employs a union panel setting and close union elections in a regression discontinuity design framework to overcome identification issues. In the panel regressions, we find that firms that are unionized and those that have higher unionization rates experience a greater frequency of quality failures. The results obtain even at a more granular establishment level in a subsample in which we can identify the manufacturing establishment associated with the recalled product. When comparing firms in close elections, we find that firms with close union wins are followed by significantly worse product quality outcomes than those with close union losses. These results are amplified in non–right-to-work states, where unions have a relatively greater influence on the workforce. We find that unionization increases firms’ costs and operating leverage and, consequently, crowds out investments that potentially impact quality. We also find some suggestive evidence that unions may compromise quality by hurting employee morale and by resisting technological upgrades in the firm. Overall, our results suggest that unions have an adverse impact on product recalls, and thus, product quality is an important dimension along which unions impact businesses. This paper was accepted by Gustavo Manso, finance.